Two chemically similar stellar overdensities on opposite sides of the plane of the Galactic disk - Bergemann, M; Sesar, B; Cohen, J; Serenelli, A; Sheffield, A; Li, T; Casagrande, L; Johnston, K; Laporte, C; Price-Whelan, A; Schönrich, R; Gould, A (Nature Publishing Group, 2018)
Our Galaxy is thought to have undergone an active evolutionary history dominated by star formation, the accretion of cold gas, and, in particular, mergers up to 10 gigayear ago. The stellar halo reveals rich fossil evidence of these interactions in the form of stellar streams, substructures, and chemically distinct stellar components. The impact of dwarf galaxy mergers on the content and morphology of the Galactic disk is still being explored. Recent studies have identified kinematically distinct stellar substructures and moving groups, which may have extragalactic origin. However, there is mounting evidence that stellar overdensities at the outer disk/halo interface could have been caused by the interaction of a dwarf galaxy with the disk. Here we report detailed spectroscopic analysis of 14 stars drawn from two stellar overdensities, each lying about 5 kiloparsecs above or below the Galactic plane – locations suggestive of association with the stellar halo. However, we find that the chemical compositions of these stars are almost identical, both within and between these groups, and closely match the abundance patterns of the Milky Way disk stars. This study hence provides compelling evidence that these stars originate from the disk and the overdensities they are part of were created by tidal interactions of the disk with passing or merging dwarf galaxies